DIREITOS HUMANOS E MEIO AMBIENTE DO TRABALHO DA MULHER: REFLEXÕES ACERCA DO PRINCÍPIO DA IGUALDADE - Ailene de Oliveira Figueiredo (TRF2, 2018)
This is an analysis of the problem of inequality on grounds of gender under the focus of sexual division of labor, from the historic survey of the rise of the feminist movement, and the implementation of the principle of equality in the United States of America (USA). Analyzes the employment relationship and other forms of social reproduction that perpetuate gender relations and explains the extent of occupational segregation and segregation of tasks in the process of work. For a better understanding and theme location in time and space are studied the emergence of the feminist movement in Brazil and their settings, as well as aspects of the sexual division of labor, as the division and precariousness of female employment and notes the need for policies effective sustainability education.